Handbook of Youth Suicide Prevention 2021
DOI: 10.1007/978-3-030-82465-5_9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patterns of Adolescent Suicide Ideation: Implications for Risk Assessment

Abstract: Understanding the nature of adolescent suicide ideation is of critical importance to improving suicide risk assessment, but research in this area has been limited. This chapter reviews theories and research suggesting that the form and pattern that adolescent suicide ideation takes can be informative about the risk of engaging in future suicidal behavior. These include studies examining suicide-related attention biases, duration of suicide ideation, and suicide-related imagery, longitudinal studies examining s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 114 publications
0
1
0
Order By: Relevance
“…The correlations between the objective measures and the psychological distress found in the current study were in the expected direction, as found in previous research (Zohar et al, 2013;Miranda et al, 2021). We found an association between suicide-related attentional bias and cardiac stress and psychological distress.…”
Section: Discussionsupporting
confidence: 91%
“…The correlations between the objective measures and the psychological distress found in the current study were in the expected direction, as found in previous research (Zohar et al, 2013;Miranda et al, 2021). We found an association between suicide-related attentional bias and cardiac stress and psychological distress.…”
Section: Discussionsupporting
confidence: 91%
“…When suicide assessments are conducted, the tools that are used have not been specifically designed for use with TAY nor validated with the population. As such, even the most commonly used tools may not accurately assess risk levels among these youth (Bernanke et al, 2017 ; Giddens et al, 2014 ; Miranda et al, 2021a , b ). Further, most suicide assessment tools lack a planning component to guide workers on the appropriate next steps depending on the assessment outcome.…”
Section: Introductionmentioning
confidence: 99%